Preparation method and application for constructing bioactive coating capable of catalytically releasing NO based on lysozyme phase transition reaction
By preparing a heparin-loaded lysozyme nanoparticle coating on the surface of the biological material and fixing selenocycinamine, a bioactive coating that catalytically releases NO is constructed, which solves the coagulation and inflammation problems of the biological material during blood contact, and achieves the good anticoagulation performance of the material and the rapid repair of the vascular endothelium.
Patent Information
- Application Number
- CN202411901325.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
During blood contact, existing biomaterials or medical devices are prone to coagulation, inflammation and intravascular dysfunction, resulting in implantation failure.
By preparing a heparin-loaded lysozyme nanoparticle coating on the surface of the matrix material and immobilizing selenocycinamine on its surface, a bioactive coating that catalytically releases NO is constructed to improve the anticoagulant properties of the material and promote vascular endothelial repair.
The good anticoagulation performance of the material and the rapid repair and regeneration of damaged vascular endothelium are achieved, reducing the risk of coagulation and inflammation after implantation, and improving the biocompatibility of the implanted material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical materials and medical devices, and specifically relates to a preparation method and application of a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction. Background Art
[0002] Biomaterials and medical devices play a very important role in the treatment, diagnosis, rehabilitation and saving of human diseases. Since the physiological reaction of the interface after the biomaterial or medical device is implanted in the human body has a very important influence on the in vivo effect of the implant, improving the performance and function of biomaterials or medical devices through surface modification is a research hotspot and a more feasible technical solution in this field. For blood-contacting materials such as intravascular implants or devices, when the implant material comes into contact with blood, it is easy to cause clinical complications such as coagulation, inflammation and intravascular dysfunction due to insufficient surface biocompatibility, which may lead to implantation failure.
[0003] In order to improve the biocompatibility of blood-contact implantable biomaterials or medical device surfaces, many researchers have used different modification techniques to design their surface properties without affecting the bulk properties of the material, so that they can undergo uniform biological reactions and obtain a uniform surface modification layer to meet the needs of specific applications. However, the current surface modification strategies have limited effects and still cannot meet the anti-coagulation and cell growth promotion properties required in a physiological environment.
[0004] Lysozyme is a functional protein that easily forms amyloid aggregates. The change of its spatial conformation can induce it to show rich phase transition behaviors under different environments, and it can form various types of assemblies such as crystals, viscous fluids, gels, and amyloid fibers. At the same time, its own protein properties also make it have good biocompatibility and degradability. The use of lysozyme phase transformation products (PTL) for surface modification of biomaterials has many advantages such as strong binding force, low cost, simple operation, mild treatment conditions, and no chemical pollution. At the same time, studies have shown that under appropriate treatment conditions, the phase transition reaction of lysozyme can form nanoparticle coatings with different sizes on the surface of the substrate material with excellent binding force. Therefore, this characteristic can be used to load bioactive molecules while forming the nanoparticle coating, thereby forming a nanoparticle coating with good biocompatibility. For example, Chinese patent CN116764002A loads a phase transition lysozyme coating on the surface of the substrate material of the vascular stent; then immerses it in a copper ion solution to obtain a copper-loaded coating; then immerses it in an activated heparin solution to obtain a coating that co-loads copper ions and heparin. In the coating prepared by the post-loading method, heparin is loaded on the surface of the coating and the loading amount is limited. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention aims to provide a preparation method and application of a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction.
[0006] The present invention first prepares a heparin-loaded lysozyme nanoparticle coating on the surface of a base material, and then fixes selenocystamine that can catalyze endogenous NO donors to release NO gas signal molecules on the surface of the material, thereby constructing a bioactive coating with catalytic NO release performance. The heparin molecules in the coating have excellent anticoagulant properties, and the grafted selenocystamine can catalyze NO donors to release NO gas molecules in vivo, further improving the anticoagulant properties of the material and inducing the repair of damaged vascular endothelial cells, thereby achieving rapid endothelialization after implantation.
[0007] Specifically, the present invention provides a method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction, comprising the following steps: S1, immersing the substrate material in a mixed solution of lysozyme, heparin and tri(2-carbonylethyl)phosphine hydrochloride (TCEP), and utilizing the phase transition reaction of lysozyme to form a heparin-loaded lysozyme nanoparticle coating; S2, washing and drying the material obtained in step S1, and then immersing it in a selenocystamine solution, adding carbodiimide (EDC) and N-hydroxysuccinimide (NHS), and grafting selenocystamine to the surface of the base material through an amidation reaction to obtain a bioactive coating that can catalyze the release of NO.
[0008] Furthermore, in step S1, the mixed solution is prepared by dissolving lysozyme, heparin, and tris(2-carbonylethyl)phosphine hydrochloride (TCEP) in a buffer solution respectively, and then mixing them in a volume ratio of 1:1:1. The buffer solution is a 4-hydroxyethylpiperazineethanesulfonic acid (HEPES) buffer solution with a pH of 6-9.
[0009] Furthermore, the concentration of the prepared lysozyme solution is 2-6 mg / mL, the concentration of the heparin solution is 1-10 mg / mL; the concentration of the tri(2-carbonylethyl)phosphine hydrochloride (TCEP) solution is 20 mM-50 mM, and the volume ratio of the lysozyme solution, the heparin solution and the TCEP solution is 1:1:1.
[0010] Furthermore, the preparation method of the heparin-loaded lysozyme nanoparticle coating in step S1 is: placing the washed and dried matrix material in a mixed buffer of lysozyme, heparin and TCEP, shaking and reacting at room temperature for 1-4 hours, and obtaining the heparin-loaded lysozyme nanoparticle coating after washing and drying.
[0011] Furthermore, in step S2, the preparation method of the selenocystamine solution is: dissolving selenocystamine in a PBS buffer solution with a pH of 7.4, adding activating agents EDC and N-hydroxysuccinimide (NHS), and shaking the reaction for 1-4 hours.
[0012] Furthermore, in step S2, the concentration of selenocystamine is 1-5 mg / mL, the molar ratio of EDC to NHS is 3-4:1, the final concentration of NHS is 2 mol / L; and the pH of the PBS buffer solution is about 7.4.
[0013] The present invention also provides the use of the bioactive coating prepared by the above method and capable of catalytically releasing NO based on the lysozyme phase transition reaction in the preparation of a vascular stent.
[0014] The present invention also provides the use of the bioactive coating prepared by the above method and capable of catalytically releasing NO based on the lysozyme phase transition reaction in the preparation of a central venous catheter.
[0015] The present invention also provides the use of the bioactive coating prepared by the above method and capable of catalytically releasing NO based on the lysozyme phase transition reaction in the preparation of artificial vascular grafts.
[0016] The present invention also provides the use of the bioactive coating prepared by the above method and capable of catalytically releasing NO based on the lysozyme phase transition reaction in the preparation of other blood contact materials.
[0017] The present invention prepares a heparin-loaded lysozyme nanoparticle coating on the surface of a biomaterial, wherein the lysozyme molecules can rapidly undergo a phase transition in an aqueous phase close to physiological conditions under the action of a reducing agent (TCEP), causing the conformation of the lysozyme molecules to change and precipitate from the solution, forming an amyloid-like product that can stably adhere to the surface of any substrate, and forming nanoparticles in the process, and in the process of forming the nanoparticles, bioactive molecules such as heparin can be loaded into the nanoparticles, thereby forming a nanoparticle coating loaded with bioactive molecules. Further, on the nanoparticle coating, selenocystamine can be grafted and fixed on the surface of the nanoparticle coating by utilizing the amidation reaction of the exposed carboxyl groups on the surface and the amino groups, and the fixed selenocystamine has an activity similar to that of glutathione peroxidase, and can catalyze NO donors in circulating blood to release NO gas signal molecules under physiological conditions, thereby further improving the anticoagulant properties of the material and inducing rapid repair and regeneration of damaged vascular endothelium.
[0018] Compared with the prior art, the present invention has the following significant advantages: (1) The present invention constructs a bioactive coating that can catalyze the release of NO based on the phase transition reaction of lysozyme, has good bonding strength with the coating, and loads heparin anticoagulant molecules during the formation of nanoparticles, thereby retaining the bioactivity of heparin to the maximum extent, thereby having good anticoagulant properties; at the same time, the present invention further grafts and fixes selenocystamine that can catalyze the release of NO gas signal molecules from endogenous donors, thereby achieving the purpose of enhancing the bioactivity of the material by utilizing the in vivo environment and endogenous bioactive molecules.
[0019] (2) The lysozyme used in the present invention has multiple biological functions such as antiviral, anti-inflammatory and immunomodulatory, and can also provide good biocompatibility for the coating prepared in the present invention.
[0020] (3) The nanoparticle coating formed by the phase transition reaction of lysozyme in the present invention has a strong bond with the substrate and can be loaded with different bioactive factors or multiple bioactive molecules at the same time, thus meeting different purposes of regulating biocompatibility.
[0021] (4) The preparation conditions of the present invention are mild, no special equipment is required, the process is simple, and the cost is low. In addition, the present invention can realize multiple physiological functions as an implant material and can be applied in cardiovascular implant materials.
[0022] (5) Since the technical solution of the present invention can form a strong nanoparticle bioactive coating on the surface of almost all solid materials, the technical solution of the present invention can be widely used in the preparation of surface coatings of different biomaterials or medical devices; at the same time, the technical solution of the present invention can form a uniform nanoparticle coating on the surface of materials or devices with different shapes, and thus has great application potential in the construction of surface coatings of implantable medical devices and is easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The scanning electron microscope morphology images of different polyurethane modified coatings prepared in Example 1 of the present invention, (a) is the surface of the polyurethane base (PU), (b) heparin-loaded lysozyme nanoparticle coating (PTL / Hep) and (c) a modified coating with selenocystamine fixed on the surface (SeCA).
[0024] Figure 2 The water contact angles of the polyurethane base layer (PU), the heparin-loaded lysozyme nanoparticle coating (PTL / Hep), and the modified coating with selenocystamine fixed on the surface (SeCA) prepared in Example 1 of the present invention.
[0025] Figure 3The hemolysis rates of the polyurethane base layer (PU), the heparin-loaded lysozyme nanoparticle coating (PTL / Hep), the modified coating with selenocystamine fixed on the surface (SeCA), and the SeCA coating under catalytic release of NO (SeCA-C) prepared in Example 1 of the present invention.
[0026] Figure 4 The GMP140 comprises a polyurethane base layer (PU) prepared in Example 1 of the present invention, a heparin-loaded lysozyme nanoparticle coating (PTL / Hep), a modified coating with selenocystamine fixed on the surface (SeCA), and a SeCA coating catalyzing the release of NO (SeCA-C).
[0027] Figure 5 The adhesion of the polyurethane base layer (PU) prepared in Example 1 of the present invention, the heparin-loaded lysozyme nanoparticle coating (PTL / Hep), the modified coating with selenocystamine fixed on the surface (SeCA), and the SeCA coating under the condition of catalytic release of NO (SeCA-C) after 1 day and 2 days of endothelial cell culture.
[0028] Figure 6 The expression of VEGF on the surface of the samples of the polyurethane base layer (PU), the heparin-loaded lysozyme nanoparticle coating (PTL / Hep), the modified coating with selenocystamine fixed on the surface (SeCA), and the SeCA coating catalyzing the release of NO (SeCA-C) after 1 day and 2 days of cell culture.
[0029] Figure 7 The NO catalytic release characteristics of the modified coatings prepared in Examples 1 and 2 of the present invention in PBS solution.
[0030] Figure 8 Polyurethane (PU), bioactive coatings prepared in Example 1 and Example 2 that can catalyze the release of NO based on the phase transition reaction of lysozyme, and blood coagulation time characterized by activated partial thromboplastin time (APTT) of the coatings prepared in Example 1 and Example 2 under the condition of catalyzing the release of NO (Example 1-C, Example 2-C). DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments and drawings. Example 1
[0032] The bioactive coating provided in this embodiment that can catalytically release NO is constructed based on the lysozyme phase transition reaction, with polyurethane as the base layer, including a heparin-loaded lysozyme nanoparticle coating and a selenocystamine layer.
[0033] The preparation method of the above-mentioned coating is as follows: polyurethane (PU) is made into a 10mm×10mm×0.3mm sample, the surface is ultrasonically cleaned with acetone and deionized water for 10 min in sequence, and then dried; then, equal volumes of 4 mg / mL lysozyme solution, 4 mg / mL heparin solution and 50 mM TCEP solution are prepared using HEPES buffer, and the pH of the TCEP solution is adjusted to 8.0. The dried polyurethane was placed in a solution of equal volumes of lysozyme, heparin and TCEP, reacted at room temperature for 2 hours, and the above steps were repeated 5 times, washed with water and blown dry to obtain heparin-loaded lysozyme nanoparticle coating (PTL / Hep); 3 mg / mL selenocystamine was then prepared with PBS, and the polyurethane coated with heparin-loaded lysozyme nanoparticles was placed in the prepared 50 mL selenocystamine solution, (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) (wt (EDC): (NHS) = 0.5751 g: 0.1150 g) were added, and fully reacted for 4 hours. After being taken out, it was rinsed with deionized water 3 times and air-dried to obtain a coating modified material (SeCA) that catalyzes the release of NO.
[0034] like Figure 1 As shown, the scanning electron microscope morphology of different polyurethane modified coatings, Figure 1 (a) It can be seen that the surface of polyurethane (PU) is smooth; Figure 1 As shown in (b), after grafting lysozyme and heparin (hep), the phase transition lysozyme coating PTL covering the smooth PU surface can be seen, showing an amyloid chain fiber network structure, and the coating is uniform and dense. Figure 1 As shown in (c), after deposition of selenocystamine (SeCA), it is basically similar to the coating of heparin-loaded lysozyme nanoparticles.
[0035] like Figure 2 As shown, the water contact angles of different samples. It can be seen that the water contact angle of the polyurethane substrate surface is about 88.8°±3.1°, and the hydrophilicity is poor; after grafting lysozyme and heparin (PTL / Hep), the water contact angle of the sample surface is reduced to 44.2°±22.21°; further, after depositing selenocystamine (SeCA) on the surface of PTL / Hep, the water contact angle of the sample surface is 36.4°±1.7°, and the hydrophilicity is further improved.
[0036] like Figure 3 The hemolysis rate of different polyurethane modified coatings is shown in the figure. It can be seen that after grafting lysozyme and heparin (PTL / Hep), the hemolysis rate of the material surface is reduced; further, after depositing selenocystamine (SeCA) on the surface of PTL / Hep, the hemolysis rate of the sample surface is further reduced; in the case of catalytic release of NO (SeCA-C), the hemolysis rate of the coating is further improved.
[0037] like Figure 4 The GMP140 results of different polyurethane modified coatings are shown in the figure. It can be seen that after grafting lysozyme and heparin (PTL / Hep), the GMP140 on the material surface decreased, inhibiting the activation of platelets; after depositing selenocystamine (SeCA) on the surface of PTL / Hep, the activation of platelets was further inhibited, showing excellent blood compatibility; in the case of catalytic release of NO (SeCA-C), the GMP140 of the coating was further reduced, indicating that NO has a positive effect on the blood compatibility of the material.
[0038] like Figure 5 As shown, after endothelial cells were inoculated on the polyurethane surface and cultured for 1 day, the number of cells adhered to the surface was small, and as time went on, the number of cells on the sample surface tended to increase; but in the case of a bioactive coating surface that could catalytically release NO based on the lysozyme phase transition reaction, the number of cells adhered to the surface increased significantly at different culture times, and the cells all extended filopodia and had good adhesion; in the case of catalytic release of NO (SeCA-C), the number of cells adhered to the coating surface further increased, showing excellent cell compatibility.
[0039] like Figure 6 As shown, the expression of VEGF on the surface of polyurethane-based (PU), heparin-loaded lysozyme nanoparticle coating (PTL / Hep), modified coating with selenocystamine fixed on the surface (SeCA), and SeCA coating under catalytic release of NO (SeCA-C) after 1 day and 2 days of cell culture. In contrast, the VEGF expression concentration on the coating surface was higher than that on the polyurethane surface, among which the amount of VEGF expressed on the surface of SeCA-C sample was the highest. The concentration of VEGF expression indicates that the endothelial cell activity on the coating surface is high and the cell function is normally expressed. Example 2
[0040] The bioactive coating for catalytically releasing NO based on the lysozyme phase transition reaction provided in this embodiment is based on polyurethane as a base layer and includes a lysozyme phase transition coating, a heparin coating and a selenocystamine layer.
[0041] The preparation method of the above-mentioned coating is as follows: polyurethane is made into a 10mm×10mm×0.3mm sample, the surface is ultrasonically cleaned with acetone and deionized water for 10 minutes in sequence, and then dried; then, equal volumes of 4mg / mL lysozyme solution and 50mM TCEP solution are prepared using HEPES buffer, and the pH of the TCEP solution is adjusted to 8.0. The dried polyurethane was placed in a solution of equal volumes of lysozyme and TCEP, reacted at room temperature for 2 hours, washed with water, and blown dry to obtain a lysozyme phase change nanoparticle coating; then an equal volume of 4 mg / mL heparin solution was prepared using PBS buffer, and (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) PBS solution (wt (EDC): (NHS) = 0.5751g: 0.1150g, 50mL) was added for activation for 15 minutes, and then the polyurethane modified with the lysozyme phase change coating was placed in the solution for full reaction for 12 hours to obtain a heparin coating; then the above coating was placed in a 3 mg / mL selenocystamine aqueous solution for full reaction for 4 hours, and after being taken out, it was rinsed with deionized water 3 times and air-dried to obtain a selenocystamine layer.
[0042] like Figure 7 As shown, the NO catalytic release characteristics of the bioactive coatings prepared by polyurethane, Example 1, and Example 2 based on the lysozyme phase transition reaction and capable of catalytically releasing NO in PBS solution. It can be seen that the bioactive coatings prepared by Example 1 and Example 2 based on the lysozyme phase transition reaction and capable of catalytically releasing NO can both catalytically release NO, and the coating prepared by Example 1 has a better effect of catalytically releasing NO.
[0043] The experimental results of hemolysis rate showed that the hemolysis rate of the bioactive coating capable of catalytically releasing NO prepared in Example 2 was 0.0240%, which was less than Figure 3 The hemolysis rate of the PU in the embodiment 1 is 0.0294%, but it is greater than the hemolysis rate of the coating prepared in Example 1 (0.0206%). This shows that the bioactive coatings prepared in Example 1 and Example 2 that can catalyze and release NO based on the lysozyme phase transition reaction can reduce the hemolysis rate of the polyurethane material, and the hemolysis rate of the coating prepared in Example 1 is lower.
[0044] like Figure 8As shown, the activated partial thromboplastin time (APTT) characterized coagulation time of polyurethane (PU), bioactive coatings prepared in Example 1 and Example 2 that can catalytically release NO based on lysozyme phase transition reaction, and coatings prepared in Example 1 and Example 2 under catalytic release of NO (Example 1-C, Example 2-C). It can be seen that the APTT values of bioactive coatings prepared in Example 1 and Example 2 that can catalytically release NO based on lysozyme phase transition reaction are higher than those of plasma, indicating that both coatings have good anticoagulant properties, among which the coating prepared in Example 1 has better anticoagulant properties. In addition, in the case of catalytic release of NO, the anticoagulant property of the coating is further improved.
[0045] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction, characterized in that: The specific steps include: S1, immersing the substrate material in a mixed solution of lysozyme, heparin and tri(2-carbonylethyl)phosphine hydrochloride, and utilizing the phase transition reaction of lysozyme to form a heparin-loaded lysozyme nanoparticle coating; S2, washing and drying the material obtained in step S1 and immersing it in a selenocystamine solution, grafting selenocystamine to the surface of the base material through an amidation reaction, and obtaining a bioactive coating that can catalyze the release of NO.
2. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 1, characterized in that: In step S1, the mixed solution is formed by mixing a lysozyme solution, a heparin solution and a TCEP solution in a volume ratio of 1:1:1, and the solvent of the lysozyme solution, the heparin solution and the tris(2-carbonylethyl)phosphine hydrochloride solution is a 4-hydroxyethylpiperazineethanesulfonic acid buffer.
3. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 2, characterized in that: The concentration of the lysozyme solution is 2-6 mg / mL, the concentration of the heparin solution is 1-10 mg / mL, and the concentration of the tris(2-carbonylethyl)phosphine hydrochloride solution is 20-50 mmol / L.
4. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 1, characterized in that: The phase transition reaction in step S1 is carried out by shaking at room temperature for 1-4 hours.
5. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 1, characterized in that: In step S2, the selenocystamine solution is prepared by dissolving selenocystamine in a PBS buffer solution, and the concentration of the selenocystamine solution is 1-5 mg / mL.
6. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 1, characterized in that: Step S2 further includes adding carbodiimide and N-hydroxysuccinimide before the amidation reaction, wherein the molar ratio of carbodiimide to N-hydroxysuccinimide is 3-4:1, and the final concentration of N-hydroxysuccinimide is 2 mol / L.
7. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 1, characterized in that: The amidation reaction described in step S2 is carried out at room temperature with shaking for 1-4 hours.
8. The method for preparing a bioactive coating capable of catalytically releasing NO based on a lysozyme phase transition reaction according to claim 1, characterized in that: The matrix material includes metal material, polymer material, inorganic non-metal material or a composite material thereof.
9. A bioactive coating capable of catalytically releasing NO prepared by the method according to any one of claims 1 to 8.
10. Use of the bioactive coating capable of catalytically releasing NO as claimed in claim 9 in vascular stents, central venous catheters and artificial vascular grafts.
Citation Information
Patent Citations
Intravascular stent coating based on phase transition lysozyme membrane loaded copper ions and heparin and preparation method of intravascular stent coating
CN116764002A